Projections of the Healthcare Costs and Disease Burden due to Hepatitis C Infection under Different Treatment Policies in Malaysia, 2018–2040 - McDonald, Scott A.; Azzeri, Amirah; Shabaruddin, Fatiha Hana; Dahlui, Maznah; Tan, Soek Siam; Kamarulzaman, Adeeba; Mohamed, Rosmawati (Springer Verlag, 2018)
Introduction: The World Health Organisation (WHO) has set ambitious goals to reduce the global disease burden associated with, and eventually eliminate, viral hepatitis. Objective: To assist with achieving these goals and to inform the development of a national strategic plan for Malaysia, we estimated the long-term burden incurred by the care and management of patients with chronic hepatitis C virus (HCV) infection. We compared cumulative healthcare costs and disease burden under different treatment cascade scenarios. Methods: We attached direct costs for the management/care of chronically HCV-infected patients to a previously developed clinical disease progression model. Under assumptions regarding disease stage-specific proportions of model-predicted HCV patients within care, annual numbers of patients initiated on antiviral treatment and distribution of treatments over stage, we projected the healthcare costs and disease burden [in disability-adjusted life-years (DALY)] in 2018–2040 under four treatment scenarios: (A) no treatment/baseline; (B) pre-2018 standard of care (pegylated interferon/ribavirin); (C) gradual scale-up in direct-acting antiviral (DAA) treatment uptake that does not meet the WHO 2030 treatment uptake target; (D) scale-up in DAA treatment uptake that meets the WHO 2030 target. Results: Scenario D, while achieving the WHO 2030 target and averting 253,500 DALYs compared with the pre-2018 standard of care B, incurred the highest direct patient costs over the period 2018–2030: US$890 million (95% uncertainty interval 653–1271). When including screening programme costs, the total cost was estimated at US$952 million, which was 12% higher than the estimated total cost of scenario C. Conclusions: The scale-up to meet the WHO 2030 target may be achievable with appropriately high governmental commitment to the expansion of HCV screening to bring sufficient undiagnosed chronically infected patients into the treatment pathway.